An Advanced Target Detection Model for Slow Moving Smaller Target in the Coastal Area - B, Rajesh; V, Udayarani; GV, Jayaramaiah (International Journal of Computer Sciences and Engineering, 2020)
Sea clutter in marine surveillance radar makes the task of detecting small targets a very challenging problem In this paper, a better model is been proposed for slow moving smaller target detection. This model initially starts with signal preprocessing to remove the basic noise then a technique called Hanning-Weighted Window Function (HWWF) assisted Time series analysis model with Spatio-Temporal Fourier Transform (STFT) for Time-Frequency analysis is applied, then a spaceTime Adaptive Processing (STAP) technique with adaptive weight and filter will be applied to perform small moving target detection under sea clutter, then at last an enhanced Antenna-Pulse-Pair Selection (APS) with Space Spectrum Correlation Coefficient (SSCC) estimation, which has been further processed for the optimal Antenna-Impulse Pair Selection that approximates clutter covariance matrix to achieve enhanced Signal-to-Clutter plus Noise Ratio (SCNR) to achieve computationally efficient STAP for moving target detection This model is proposed for multiple (moving) sea-target detection in sea clutter and jamming probable environment. The overall proposed model will be developed based on impulse radar setup using MATLAB tool Thus, it is well suited for slow moving small target detection under sea clutter for efficient coastal surveillance purposes.